The Impact of Foreign Direct Investment on Wages and Working Conditions - Arnal, Elena (OECD Publishing, 2008)
Foreign direct investment (FDI) by OECD-based multinational enterprises (MNEs) in developing and emerging economies has increased dramatically over the past two decades. While generally perceived as beneficial for local development, it has also raised concerns about unfair competition and the protection of workers' rights in host countries. This paper documents the recent increase in FDI and assesses its effects on wages and working conditions for workers of foreign affiliates of MNEs and those of their independent supplier firms. The evidence suggests that MNEs tend to provide better pay than their domestic counterparts, especially when they operate in developing and emerging economies. The positive impact on wages also appears to spread to the employees of domestic firms that serve as suppliers of MNEs or recruit managers with prior experience in foreign firms, but these spillover effects are small. MNEs also provide more training than domestic firms, but it is unclear whether this reflects a causal impact of foreign ownership
Keywords: Social Issues/Migration/Health